Effect of acid treatment for reducing pores clogging in polyvinyl alcohol grinding stone / Nurul Syafiqah binti Hasni. - Nurul Shafiqah Hasni (School of Materials Engineering, Universiti Malaysia Perlis, 2017)
The objectives of this research proposal are ; to investigate the pores properties of control PVA grinding stone and sample PVA grinding stone after grinding operations ; to investigate the effect of different acids with different molarities and stirring times on the pores debris removal from control and sample PVA grinding stone ; to find the optimum parameter for debris removal using acid solution in the shortest treatment time without damaged the structure of PVA grinding stone.